Differential responses of Bradyrhizobium sp. SUTN9-2 to plant extracts and implications for endophytic interactions within different host plants - Teerana Greetatorn; Pakpoom Boonchuen; Pongdet Piromyou; Pongpan Songwattana; Jenjira Wongdee; Kamonluck Teamtisong; Nantakorn Boonkerd; Shusei Sato; Neung Teaumroong; Panlada Tittabutr (Scientific Reports)
Abstract Bradyrhizobium sp. strain SUTN9-2 demonstrates cell enlargement, increased DNA content, and efficient nitrogen fixation in response to rice (Oryza sativa) extract. This response is attributed to the interaction between the plant’s cationic antimicrobial peptides (CAMPs) and the Bradyrhizobium BacA-like transporter (BclA), similar to bacteroid in legume nodules. The present study reveals that SUTN9-2 can also establish functional endophytic interactions with chili (Capsicum annuum) and tomato (Solanum lycopersicum) plants. When exposed to extracts from chili and tomato, SUTN9-2 exhibits cell elongation, polyploidy, and reduced cell viability, with the effects being less pronounced for tomato extract. Transcriptomic and cytological analyses revealed that genes associated with CAMP resistance, nitrogen metabolism, nitrogen fixation, defense responses, and secretion systems were upregulated, while genes related to the cell cycle and certain CAMP-resistance mechanisms were downregulated, particularly in response to chili extract. This study suggests that SUTN9-2 likely evolves resistance mechanisms against CAMPs found in rice, chili, and tomato plants through mechanisms involving the protease-chaperone DegP, AcrAB-TolC multidrug efflux pumps, and polysaccharides. These mechanisms facilitate efflux, degradation, and the formation of protective barriers to resist CAMPs. Such adaptations enable SUTN9-2 to persist and colonize host plants despite antimicrobial pressures, influencing its viability, cell differentiation, and nitrogen fixation during endophytic interactions with various plant hosts.